2022
DOI: 10.3390/nu14040764
|View full text |Cite
|
Sign up to set email alerts
|

Pasteurized Akkermansia muciniphila Ameliorate the LPS-Induced Intestinal Barrier Dysfunction via Modulating AMPK and NF-κB through TLR2 in Caco-2 Cells

Abstract: Akkermansia muciniphila is well known for the amelioration of inflammatory responses and restoration of intestinal barrier function. The beneficial effect of A. muciniphila occurred through contacting Toll-like receptor 2 (TLR2) on intestinal epithelial cells by wall components. In this case, the downstream mechanism of pasteurized A. muciniphila stimulating TLR2 for ameliorated intestinal barrier function is worth investigating. In this study, we evaluated the effect of live and pasteurized A. muciniphila on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 45 publications
(70 reference statements)
0
30
0
Order By: Relevance
“…We considered that orlistat increased the relative abundance of Akkermansia (Fig. 8g), which improved the damaged intestinal barrier; 57 therefore, it prevented LPSs from entering the circulatory system. Psyllium husk had a better effect at reducing the serum LPS level than orlistat (HFD + PH and HFD + orlistat, 0.74-fold, P = 0.015, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We considered that orlistat increased the relative abundance of Akkermansia (Fig. 8g), which improved the damaged intestinal barrier; 57 therefore, it prevented LPSs from entering the circulatory system. Psyllium husk had a better effect at reducing the serum LPS level than orlistat (HFD + PH and HFD + orlistat, 0.74-fold, P = 0.015, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Pasteurized A. muciniphila was shown to attenuate inflammatory response and improve intestinal barrier integrity. This is probably due to stimulating AMP-activated protein kinase (AMPK) and inhibiting Nuclear Factor-Kappa B (NF-kB) activation through the stimulation of TLR2 on intestinal epithelial cells (140). Aiming to understand the mechanisms of A. muciniphila involved in modulating the host metabolism, Yoon et al identified a protein named P9 which induces glucagon-like peptide-1 (GLP-1) secretion and brown adipose tissue thermogenesis (141).…”
Section: Mice Modelsmentioning
confidence: 99%
“…In addition, as compared to pasteurized cells, live A. muciniphila was found to have a greater effect on improvement of the gut microbiota composition in mice, reducing the relative abundance of pathobionts while increasing the relative abundance of symbionts (Raftar et al 2021. Lastly, in Caco-2 cells, a difference was found in the expression of tight-junction protein claudin1, which was increased greater in the presence of live cells as opposed to pasteurized A. muciniphila cells (Shi et al 2022). Even though some differences have been observed…”
Section: Pasteurized Vs Live a Muciniphilamentioning
confidence: 89%
“…These parameters included greater effects in metabolic parameters, preventing the onset of obesity, strengthening gut barrier function, and maintaining immune homeostasis in mice, as well as upregulation of tight-junction proteins and regulation of immune response-related genes in Caco-2 cell lines. In contrast, greater effects of live A. muciniphila have also been reported , Shi et al 2022. In mice, live cells were shown to have greater effects on the modulation of gene expression related to fatty acid synthesis, energy homeostasis and immune response in the liver .…”
Section: Pasteurized Vs Live a Muciniphilamentioning
confidence: 97%
See 1 more Smart Citation